Attitudes and beliefs of patients and primary caregivers towards deprescribing in a tertiary health care facility - Narayan Gaurang; Rajendran Priyadharsini; Kandan Balamurugesan; Mathiyalagen Prakash; Devanathan Reka (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Background: Good prescribing practices form the essence of drug therapy for better patient care. The major aim of better prescribing is to improve rational prescribing. Deprescribing gained momentum in recent decades. Objective: This study aimed to explore the attitude and beliefs of deprescribing among patients and their caregivers forming dyads in a tertiary health care facility. Methods: Cross-sectional, questionnaire-based prospective study done for two months. Attitude towards deprescribing was assessed by using validated rPATD (revised Patient attitude towards deprescribing) questionnaire. Cohen's kappa coefficient was used to measure the agreement between the views of people and their caregivers forming dyads about medication cessation. Results: 312 patients and caregivers (156 forming dyads) participated in the study. Among 156 patients, 25.6% were hypertensives & 21.2% had diabetes. 41.7% were between 36-50 years of age. Only 16.7% belong to the elderly age group. 2.5% were taking >5 medications. 43.6% of patients and 62.2% of caregivers were female. 51.3% of the patients were willing to stop one or more of their regular medicine(s) under the treating physician's advice, but 62% were satisfied with their current medicine(s). 33.4% were reluctant to stop taking medicines for a long time. Conclusions: In our study, more than 50% of people and their caregivers were willing to try medication cessation under their physician's recommendation. There was moderate agreement between patients and their caregivers in the trial of medication cessation. Thus, the results obtained from this study may help towards improving rationalized prescribing practices in the institutional setup.